Reprogramming Intestinal Epithelial Cell Polarity by Interleukin-22 - Delbue, Deborah; Lebenheim, Lydia; Cardoso-Silva, Danielle; Dony, Violaine; Krug, Susanne M.; Richter, Jan F.; Manna, Subhakankha; Muñoz, Melba; Wolk, Kerstin; Heldt, Claudia; Heimesaat, Markus M.; Sabat, Robert; et al. (Frontiers in Medicine, 2021)
Interleukin-22 (IL-22) impacts the integrity of intestinal epithelia and has been associated with the development of colitis-associated cancer and inflammatory bowel diseases (IBD). Previous data suggest that IL-22 protects the mucosal barrier and promotes wound healing and barrier defect. We hypothesized, that IL-22 modulates cell polarity of intestinal epithelial cells (IECs) acting on tight junction assembly. The aim of the study was to investigate IL-22-dependent mechanisms in the reprogramming of intestinal epithelia. IECs were exposed to IL-22 at various concentrations. IECs in Matrigel® were grown to 3-dimensional cysts in the presence or absence of IL-22 and morphology and expression of polarity proteins were analyzed by confocal microscopy. Epithelial cell barrier (TER and sandwich assay) and TJ assembly analysis (calcium-switch assay) were performed. TJ and cell polarity protein expression were assessed by western blotting and confocal microscopy. Cell migration and invasion assays were performed. Induction of epithelial-mesenchymal transition (EMT) was assessed by RT-qPCR analysis and western blotting. Signaling pathway analyses were performed by phosphoblotting and functional assays after blocking STAT3 and ERK signaling pathways. Using the toxoplasma-model of terminal ileitis, IL-22-knock-out mice were compared to wild-type littermates, analyzed for barrier function using one-path-impedance-analysis and macromolecular flux (H3-mannitol, Ussing-chambers). IECs exhibited a barrier defect after IL-22 exposure. TJ protein distribution and expression were severely impaired. Delayed recovery in the calcium-switch assay was observed suggesting a defect in TJ assembly. Analyzing the 3D-cyst model, IL-22 induced multi-lumen and aberrant cysts, and altered the localization of cell polarity proteins. Cell migration and invasion was caused by IL-22 as well as induction of EMT. Interestingly, only inhibition of the MAPK pathway, rescued the TJal barrier defect, while blocking STAT3 was relevant for cell survival. In addition, ileal mucosa of IL-22 deficient mice was protected from the barrier defect seen in Toxoplasma gondii-induced ileitis in wild type mice shown by significantly higher Re values and correspondingly lower macromolecule fluxes. IL-22 impairs intestinal epithelial cell barrier by inducing EMT, causing defects in epithelial cell polarity and increasing cell motility and cell invasion. IL-22 modulates TJ protein expression and mediates tight junctional (TJal) barrier defects via ERK pathway.